Adjunctive Orthodontic Treatment with Lingual Orthodontic System - Kafle, D; Humagain, M; Upadhaya, C (Kathmandu University Medical Journal, 2012)
The lingual orthodontic therapy though started in 1972, could not be popular till the beginning of 1990. In Nepal it does not have a history of more than a year. It is started in Dhulikhel Hospital for the first time in Nepal. Usually orthodontic therapy is meant for putting braces on the labial surface of the teeth which is called labial orthodontic system. Lingual orthodontic system is a purely invisible kind of orthodontic therapy in which braces are placed behind the teeth. The advantages of lingual orthodontic therapy are: invisibility, better biomechanics and improved patient compliance. On the other hand it is difficult to master and costlier than labial orthodontics. We have presented six adjunctive orthodontic cases treated by lingual system with the same end result comparable to labial orthodontic system. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6351 Kathmandu Univ Med J 2011;9(4):306-9